2006
DOI: 10.1063/1.2188085
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond time scale, high power electrical wire explosion in water

Abstract: Experimental and magnetohydrodynamic simulation results of nanosecond time scale underwater electrical explosions of Al, Cu, and W wires are presented. A water forming line generator with current amplitude up to 100kA was used. The maximum current rise rate and maximum Joule heating power achieved during wire explosions were dI∕dt⩽500A∕ns and 6GW, respectively. Extremely high energy deposition of up to 60 times the atomization enthalpy was registered compared to the best reported result of 20 times the atomiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 22 publications
5
54
0
Order By: Relevance
“…Different plasma characteristics are visible on the features of the recorded light including the shock wave and the plasma channel. 16,17 We present here the measures of the exterior front radii as a function of time that include the expansion plasma and the shock wave stages. One of the most visible features is the reduction of the light absorption region at the beginning of the plasma expansion when the initial charging voltage increases its magnitude; 6 also, an increase in the rate of the radii of the shock wave is visible.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Different plasma characteristics are visible on the features of the recorded light including the shock wave and the plasma channel. 16,17 We present here the measures of the exterior front radii as a function of time that include the expansion plasma and the shock wave stages. One of the most visible features is the reduction of the light absorption region at the beginning of the plasma expansion when the initial charging voltage increases its magnitude; 6 also, an increase in the rate of the radii of the shock wave is visible.…”
Section: Results and Analysismentioning
confidence: 99%
“…Because the shock wave generated has rich information about the shock wave generator system, different wire materials, dimensions, and surrounding media were studied in the past. [14][15][16][17][18] Here, we focus the study on a copper exploding wire at atmospheric pressure. The diameter of wire and charged voltage of the electrical system are used simultaneously as parameters in these experiments.…”
Section: Introductionmentioning
confidence: 99%
“…2D r-θ Lagrangian hydrodynamics simulations were compared with the trajectory of the shockwave to estimate the parameters including the pressure, density, temperature and energy density in the water behind the shock 22,23 . The simulations were based on the finite volume method and included conservation of mass, momentum and energy coupled with high pressure equations of state for copper and water.…”
Section: Simulations Of the Shockwave Implosionsmentioning
confidence: 99%
“…The plasma shell forces the current away from the wire core and reduces joule energy deposition. On the other hand, Grinenko et al (4) reported that the plasma shell was significantly reduced for wires exploded in water, resulting in significant energy deposition. Clearly, to improve energy deposition, it is necessary to minimize current diversion from the wire core to the plasma shell during wire explosion.…”
Section: Introductionmentioning
confidence: 99%
“…In a number of papers, attempts were made to study the influence of a surrounding medium on the energy deposited during electrical wire explosions (1)(2)(3)(4). A recent report by Sarkisov et al (3) on the electrical explosion of titanium wires showed that the energy deposited into the wire doubled for explosions in air when compared to that deposited for explosions in vacuum.…”
Section: Introductionmentioning
confidence: 99%